Nest Associated Mites (Acari: Winterschmidtiidae) of Stingless Bee Tetragonula fuscobalteata in Central Sulawesi, Indonesia - Nurly Maftukhah; I Made Budiarsa; Manap Trianto; Masrianih Masrianih; Rafiqah Rafiqah; Fatmah Dhafir (Biology, Medicine, & Natural Product Chemistry, 2026)
Stingless bees are essential pollinators in tropical ecosystems and play an important role in sustaining biodiversity and agricultural productivity. In Central Sulawesi, Indonesia, Tetragonula fuscobalteata is widely cultivated in small-scale meliponiculture systems. However, information regarding mites associated with its nests remains limited. This study aimed to identify and describe nest-associated mites found in T. fuscobalteata colonies. The research was conducted in Dolago Village, Parigi Moutong Regency, Central Sulawesi. Nest samples were collected from five active colonies. Mites were observed under a stereo microscope, collected using a fine brush, and mounted on slides with polyvinyl alcohol. Identification was based on morphological characteristics using standard taxonomic keys, and morphometric measurements were obtained using Image Raster 3.0. All specimens were identified as deutonymphs of the genus Saproglyphus (Acari: Winterschmidtiidae). Mites were found in storage pots and cerumen structures but were absent from brood cells. The deutonymphs exhibited a well-developed sucker plate, reduced chelicerae, and fused coxae III, indicating phoretic adaptation. The mean body length was 192.72 ± 22.14 µm and width was 145.78 ± 12.62 µm. These findings provide baseline data on mite associations in T. fuscobalteata nests and contribute to understanding arthropod interactions in meliponiculture systems.